Community engagement, solidarity, and citizenship - Abenir, Mark Anthony D. (Makati City : Diwa Learning Systems, Inc., 2020)
"We cannot seek achievement for ourselves and forget about progress and prosperity for our community... Our ambitions must be broad enough to include the aspirations and needs for others, for their sakes and for our own. Community Engagement, Solidarity, and Citizenship (Second Edition), reflects the famous quote of Chavez as it is especially designed to raise the consciousness of learners to think critically about current social issues and collectively engage in worthwhile activities that will benefit various vulnerable sectors and communities of the society".
Includes bibliography.
English text.
Keywords: Service training -- Philippines; Student activities -- Philippines; Community and school -- Philippines